Superconductivity induced by carrier injection into non-superconducting Bi2Sr2CaCu2O8+δ - Simsek, Yilmaz; Koval, Yury; Gieb, Klaus; Müller, Paul (Superconductor Science and Technology, 2014)
Doping by carrier injection was investigated in strongly oxygen-depleted Bi2CaCu8 + δ. In order to perform four point c-axis measurements in non-superconducting samples, a new fabrication technique was developed. We were able to show that non-superconducting Bi 2CaCu8 + δ can be converted into a superconducting, even overdoped state only by applying a large bias current along the c-axis. A critical temperature of 91 K and a c-axis critical current density of 2000 A cm were achieved. Moreover, the doping effect is persistent and reversible resembling the resistive-memory switching effect observed earlier in various oxides. The mutual influence of oxygen doping and change of the charge carrier concentration by carrier injection is discussed. © 2014 IOP Publishing Ltd.
Keywords: Bi2212; charge carrier injection; doping; intrinsic Josephson junctions; superconductivity